PROFILING OF THE HOB TOOL FOR WORM SHAFTS DEFORMATION - VIRGIL GABRIEL TEODOR; GEORGIANA-ALEXANDRA MOROSANU; NICUSOR BAROIU; RAZVAN SEBASTIAN CRACIUN; VIOREL PAUNOIU (Journal of Engineering Studies and Research)
The paper presents an algorithm for profiling the hob tool designed to generate by plastic deformation the worm shafts from the composition of worm-wheel gear type, used in the seat adjustment mechanisms of some Audi and Mercedes cars. The active surface of the hob tool is a cylindrical helical surface of constant pitch. Two such tandem tools are used for deformation, the semi-finished product being positioned between them. During generation, the tools rotate around their own axes, which, combined with their helical surface, causes a helical movement of the blank. The active surfaces of the tools are mutually winding on the helical flanks of the generated worm. In the paper, two applications were developed for the generation of worms whose dimensions were determined by 3D scanning.